Development of contact displacement sensor based on frequency-modulated continuous-wave. Issue 19 (10th November 2020) - Sun, Bin; Zheng, Gang; Zhang, Xiongxing; Bai, Lang
Abstract : Frequency-modulated continuous-wave(FMCW) interference measurement has the advantages of length traceability, large range, high precision, simple structure and optical fibre transmission. Based on the characteristics of the axial inductance sensor, a novel laser interference displacement sensor is developed. The formula of FMCW laser ranging is derived in detail and the mechanical structure and optical system of the contact displacement sensor are designed. Integrating the interferometric optical path into the sensor rod, converting non-contact measurement with cooperative targets into contact measurement can realize direct measurement of workpieces with complex surface conditions on the production line, such as free-form surfaces and oily surfaces. This technology expands the application of optical non-contact measurement. Experimental results show that the designed displacement sensor can reach a measuring range of 15 mm with a standard deviation of less than 0.01μm. It can meet the requirements of large-scale and high-precision inspection applications in the field of precision manufacturing.